2015
DOI: 10.17969/agripet.v15i2.2849
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kualitas Ampas Tebu Sebagai Pakan Ternak Melalui Fermentasi dengan Penambahan Level Tepung Sagu yang Berbeda

Abstract: Feed plays an important role in livestock production system. Due to limitation of pasture and forege areas, it needs to find new feed alternative as replacement of forage as animal feed. One of feed alternatives as replacement of forage is bagasse. Bagasse has low nutritive content and digestibility. One of the efforts to improve bagasse quality is by fermentation. The purpose of this experiment was to improve nutritive values of bagasse by fermentation method by using Trichoderma harzianum as inoculum. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…Thus microbial worked during the fermentation process was more optimal in degrading cassava peel so that more organic matter were degraded and the ash content decreased. This was in accordance with research by [9] and [10].…”
Section: Ash Contentsupporting
confidence: 94%
“…Thus microbial worked during the fermentation process was more optimal in degrading cassava peel so that more organic matter were degraded and the ash content decreased. This was in accordance with research by [9] and [10].…”
Section: Ash Contentsupporting
confidence: 94%
“…Agro-industrial by products as an alternative feedstuff have been used as animal feed to reduce feed cost (Mirzaei-Aghsaghali and Maheri-Sis, 2008;Samadi et al, 2015a;Samadi et al, 2015b). Agro-industrial by products is also a potential solution to provide protein and calories for animal production in worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…However, agricultural and agro-industrial by product feed conteined high percentage of fiber and difficult to be digested by animals (Suwandyastuti and Rimbawanto, 2011). Researchs conducted by scientiests indicated that pre-treatment of high fiber feed were able to improve nutrient content and digestibility of feed (Bisaria et al, 1997;Tang et al, 2008;Wanapat et al, 2009 ;Rahman et al, 2011 ;Shrivastava et al, 2011 ;Wajizah et al, 2015 ;Samadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%